Građevni i urbanistički propisi u Hrvatskoj od 1956. do 1971. godine Building and Town-Planning Regulations in Croatia from 1956 to 1971 - Kahle, Darko (2021)
U članku se opisuju i komparativno analiziraju građevni i urbanistički propisi u Hrvatskoj od 1956. do 1971., kad je načelno dovršen zakonodavni okvir jugoslavenskih i hrvatskih građevnih propisa. Analizirani propisi, koji su prvi put bili stručno publicirani u repetitoriju 1956. godine, ambivalentno su nastajali na službenoj negaciji građevnoga zakonodavstva Kraljevine Jugoslavije 1946. i neslužbenom korištenju većine ukinutih propisa sve do kraja 1960-ih. Kolokvijalno poznati pod suvremenim pojmom građevinska regulativa, analizirani propisi pokazuju određenu tehničku kompetentnost u člancima koji nisu zadirali u socijalističko društveno uređenje, ali i potpunu ovisnost o tom uređenju u ostalim paragrafima, poput procedura upravnoga postupka ili toleriranja bespravne izgradnje.
The building regulation system that was initiated in 1850 with the adoption of the "Regulation on the Admission of Civil Engineering Students and the Introduction of State Examinations in Civil Engineering" in the Austrian Empire was repealed in 1946, through the "Law on the Invalidity of Legal Regulations Adopted Before 6 April 1941 and During the Enemy Occupation". The new socialist building regulation system was created through the regulations of the Yugoslav government from 1947 on; it was acceptable to use certain repealed regulations until new ones were enacted, provided they did not conflict with the newly-created socialist legal system of the Federal People"s Republic of Yugoslavia. After the Federal Ministry of Construction was abolished in 1950, the technical regulations and standards were regulated at the federal level, while the administrative procedures and other legal regulations were gradually lowered to the level of the republics, including Croatia. So as to help architects, spatial planners, and other experts in the building process orient themselves in this jungle of regulations, architect Vladimir Šilhard (Schilchard) published the Revision Book of Building Regulations and Procedure in the P. R. of Croatia in the professional journal Čovjek i prostor (Man and Space) in 1956. This article also exhaustively presents and analyses the building regulations in the period from 1946, through Šilhard"s unified compendium, to the enactment of the Zagreb City Master Plan in 1971. On the one hand, the 1960s period was a great challenge for adopting regulations, primarily due to the new way of building residential buildings, which were not encompassed by the then existing regulations. On the other hand, new urban legislation was needed after Zagreb spread over the river Sava to the south, where the Zagreb Fair and the first residential neighbourhoods were built, so that the city could maintain a sustainable appearance of mod
Bibliografija
Summary.
Keywords: građevno zakonodavstvo, građevni propisi, urbanistički propisi, Hrvatska, Zagreb, 1956. – 1971., građevinska regulativa